Peran Orangtua untuk Menstimulasi Literasi Permulaan pada Anak Usia Pra Sekolah - Santoso, Sandy Tegariyani Putri; Jaya, Tiara Juliana (Universitas Nusantara PGRI Kediri, 2023)
Literacy in early childhood is not only limited to the ability to read and write but also to read symbols or signs that are around children. Sensitivity to signs in the surrounding environment is the initial ability to read more complex symbols such as letters of the alphabet. Family and home are the first places for children to learn, but not all families, in this case parents, understand this. Parents still think that later literacy activities will be carried out by their children. This training activity aims to provide information and invite parents to be more aware that literacy activities can be started with the simplest activities at home. This community service activity is carried out using the in-service training method. After the parent service activities, posyandu cadres, and PAUD post teachers have an understanding that literacy stimulation activities can be done at home, and have new knowledge about various activities that can be done to stimulate early literacy in children. PAUD can socialize various activities to stimulate early literacy through posters and booklets that have been distributed in community service activities.